Geological-Geophysical Investigations in the North Atlantic during Cruise 53 of the R/V Akademik Sergey Vavilov - Skolotnev, SG; Peyve, AA; Sanfilippo, A; Ivanenko, AN; Ligi, M; Veklich, IA; Petracchini, L; Ponomarenko, EP; Basch, V; Kuleshov, DA; Ferrando, C; Dobrolyubov, VN; et al. (Oceanology, 2022)
We provide information on geological and geophysical investigations of the structure of the area between the Bight and Charlie Gibbs transform faults in the North Atlantic during cruise 53 of the R/V Akademik Sergey Vavilov in September-October 2021. The structure of the Eastern Tula Rise is also considered. The preliminary results of the expedition are discussed.